2004
DOI: 10.1101/gr.1396104
|View full text |Cite
|
Sign up to set email alerts
|

Global Survey of Chromatin Accessibility Using DNA Microarrays

Abstract: An increasing number of studies indicate a central role for chromatin remodeling in the regulation of gene expression. Current methods for high-resolution studies of the relationship between chromatin accessibility and transcription are low throughput, making a genome-wide study impractical. To enable the simultaneous measurement of the global chromatin accessibility state at the resolution of single genes, we developed the Chromatin Array technique, in which chromatin is separated by its condensation state us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…DNA inaccessibility is thought to restrict recognition of DNA templates by regulatory proteins and thus to hinder transcription while accessible chromatin structures may facilitate transcription 15,26 . It is also possible that increased DNA accessibility is a consequence of transcriptional activity.…”
Section: Resultsmentioning
confidence: 99%
“…DNA inaccessibility is thought to restrict recognition of DNA templates by regulatory proteins and thus to hinder transcription while accessible chromatin structures may facilitate transcription 15,26 . It is also possible that increased DNA accessibility is a consequence of transcriptional activity.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, the chromatin sensitivity was analyzed for two silent transposable element (TE) genes (Ta2 and Cinful-like) and two active genes (GAPDHa and ACTIN7 [ACT7]) in Arabidopsis. We and others have shown that transcription is generally associated with accessible chromatin (Weil et al, 2004;Boyle et al, 2008;Bell et al, 2010;Shu et al, 2012;Zhang et al, 2012). Thus, we predict that the two TE genes should be much less sensitive to DNase I than the two active genes and, therefore, can be used as insensitive and sensitive controls in future assays.…”
Section: Analysis Of Digested Dna By Pcrmentioning
confidence: 99%
“…Therefore, analysis methods based on PCR have been developed (Pfeifer and Riggs, 1991;Feng and Villeponteau, 1992;McArthur et al, 2001;Dorschner et al, 2004;Martins et al, 2007). In recent years, DNase I assays were coupled to high-throughput genome-wide profiling strategies such as genome tiling arrays and next-generation sequencing (Crawford et al, 2004(Crawford et al, , 2006Sabo et al, 2004Sabo et al, , 2006Weil et al, 2004). While much has been learned about the accessibility of chromatin in animal and yeast systems, our knowledge of chromatin accessibility in plants is limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies of nucleosomal positioning have been carried out for individual genomic regions, indicating that positioning can be both flexible and constrained (e.g., Lu et al 1994;Kornberg and Lorch 1999;Sekinger et al 2005). Recently, these studies have been extended genomewide through the analysis of populations of nucleosomes using high-density microarrays (for the yeast Sacchromyces cerevisiae) (Yuan et al 2005) and using the Chromatin Array technique (for human cell lines) (Weil et al 2004). These studies have shed considerable light on DNA sequence and other factors influencing nucleosome occupancy; certainly the results serve as a strong argument for pursuing a genome-wide analysis of nucleosome positioning and dynamics at an increasingly detailed level (Satchwell et al 1986;Dong et al 1990;Lu et al 1994;Travers and Muyldermans 1996;Flaus and Richmond 1998;Crawford et al 2006).…”
mentioning
confidence: 99%